Gestão da informação e comunicação interna: análise do prontuário clínico em uma faculdade de odontologia - Andrade, Talita Araújo de (2023)
Information management and internal organizational communication are important factors for greater efficiency in the services provided by public institutions, including health institutions. Health information technologies can be an alternative for improving current processes, bringing benefits to management, information flows, internal communication, teaching and research. With this in mind, this work deals with a diagnosis of information and communication management from the perspective of the clinical medical records used in the UFRN Department of Dentistry, with the aim of mapping out how the process takes place and assessing the level of satisfaction of the students, teachers and administrative staff involved, to find out whether the current process meets administrative, teaching and research needs and assuming that, if necessary, electronic medical records could be an alternative to bring improvements to the process currently used. For the research, a bibliographical and descriptive study was carried out, which is also classified as action research. To achieve the objectives, a questionnaire was applied with questions about user characterization, level of satisfaction on the Likert scale and basic questions about technologies and electronic medical records, most of which were closed, classifying the study as quantitative or mixed method. To process the data, the Jamovi statistical software was used to obtain frequency and percentage values, where the Kruskal-Wallis test and the Dwass-Steel-Chritchlow-Fligner post-hoc test were also carried out to make multiple comparisons between the groups interviewed and the level of satisfaction. Based on the data obtained from both the closed and open questions, it was found that the majority of respondents were dissatisfied, with internal communication being the most frequently addressed issue, and it was concluded that, at the moment, the analog medical records process is not meeting all the needs of the department and its members. As a result, some changes were recommended in order to achieve improvements.